2022
DOI: 10.1038/s41598-022-21095-6
|View full text |Cite
|
Sign up to set email alerts
|

Phase angle obtained via bioelectrical impedance analysis and objectively measured physical activity or exercise habits

Abstract: The phase angle (PhA), measured via bioelectrical impedance analysis, is considered an indicator of cellular health, where higher values reflect higher cellularity, cell membrane integrity, and better cell function. This study aimed to examine the relationship between PhA and exercise habits or objectively measured physical activity. We included 115 people aged 32–69 years. The body composition and PhA were measured using a bioelectrical impedance device. Physical activity and sedentary behavior (SB) were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
3
20
1
Order By: Relevance
“…Furthermore, in the present study, a signi cant positive correlation was found between PhA and LSA, which is an indicator of physical activity. High physical activity is associated with high physical function, and a correlation between physical activity and PhA has been reported in other studies 18,29 . However, the mechanisms underlying the relationship between physical activity, physical function, and PhA are unknown.…”
Section: Relationship Between Pha Physical Function and Physical Acti...supporting
confidence: 70%
“…Furthermore, in the present study, a signi cant positive correlation was found between PhA and LSA, which is an indicator of physical activity. High physical activity is associated with high physical function, and a correlation between physical activity and PhA has been reported in other studies 18,29 . However, the mechanisms underlying the relationship between physical activity, physical function, and PhA are unknown.…”
Section: Relationship Between Pha Physical Function and Physical Acti...supporting
confidence: 70%
“…These situations correlate with an increased mortality rate and the length of the hospital stay [ 52 , 53 , 54 ]. While many studies have been conducted on healthy subjects, obese individuals, the elderly population, and hemodialysis patients, we need more data on metabolic surgery diabetes remission patients [ 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PhA correlates well with skeletal muscle density measured using computed tomography 26 . PhA measurements were performed using a bioelectrical impedance spectroscopy device (SFB7, ImpediMed, Pinkenba, Australia) 27 …”
Section: Methodsmentioning
confidence: 96%
“…26 PhA measurements were performed using a bioelectrical impedance spectroscopy device (SFB7, ImpediMed, Pinkenba, Australia). 27…”
Section: Measurement Of Skeletal Muscle Mass and Qualitymentioning
confidence: 99%